Follow-Up Studies of cf-DNA Testing from 101 Consecutive Fetuses and Related Ultrasound Findings - Basaran, Seher; Has, Recep; Kalelioglu, Ibrahim Halil; Karaman, Birsen; Kirgiz, Melike; Dehgan, Tahir; Satkin, Bilge Nihan; Sivrikoz, Tugba Sarac; Yuksel, Atil (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To determine the true- and false-positive rates of cf-DNA testing in a cohort of patients from tertiary care centers and assess the impact of ultrasound examinations in pregnancy management.Materials and Methods Clinical, cytogenetic and ultrasound data of 101 consecutive fetuses were collected retrospectively. Cases were classified into five groups according to the ultrasound findings. Karyotyping, interphase FISH and microarray techniques were used for follow-up studies.Results The overall false-positive rate was low for trisomy 21 (T21, 8.2 %), but significantly higher for trisomy 18 (T18, 40 %), monosomy X (MX, 50 %), X/Y trisomies (57.1 %), trisomy 13 (T13, 71.4 %). While single cases of trisomy 16, trisomy 22 and 8q duplication positive in cf-DNA were confirmed, 3 microdeletions (1p36 and two 22q11.2) were not. About 75 % of confirmed T21’s and all confirmed T18 and T13 had major markers and/or malformations. While false-negative cases (two T21, one T18 and one T13) were identified due to abnormal ultrasound findings, all false-positive cases were normal sonographically. Ultrasound findings of confirmed trisomy 16, 22, dup8q, monosomy X and other X/Y aneuploidies were unspecific. Term placenta studies were helpful to assess the role of confined mosaicism in unconfirmed cf-DNA test results. A vanishing twin has been observed as the likely cause of one false-positive T18.Conclusion Our study contributes clinical data on discrepant cf-DNA testing results, corroborates the need for confirmational invasive testing and underscores the benefit of expert ultrasound in the prevention of fatal diagnostic errors.
Keywords: cf-DNA; false positive; false negative; ultrasound; follow-up